FINDING THE PSYCHOLOGICAL AND SOCIAL DYNAMICS IN KAMAL SULEIVANI'S NEY YA BENDEMANÊ (THE WAITING NAIL) BASED ON ALFRED ADLER’S THEORY - Ahmed, Diler (Humanities Journal of University of Zakho, 2024)
Based on literary theory, the novel titles Ney ya Bendemanê has a strong relationship with society and individuals. The novel often becomes a mirror of the society, in which many complex dynamics are displayed between individuals and their communities, reflecting the psychological dimensions and the extent to which they affect individuals' behaviors and feelings within their social environments. In the light of this literary vision, this research attempts to analyze Kamal Suleivani's novel Suleivani's Ney ya Bendemanê (The Waiting Nail), according to the psychosocial dimensions of the protagonists, which prompted the writer to use the novel's artistic techniques, writing his novel from a socio-psychological point of view, in a way that reflects the individual's life and the social conditions in which he lives. For this purpose, the novel was used by Suleivani's novel Ney ya Bendemanê (The Waiting Nail) based on Alfred Adler’s Theory to conduct an article entitled Finding the Psychological and Social Dynamics in the novel. The researcher resourced the psychoanalytic theory of the character Alfred Adler in writing this research, because this theory emphasizes the close relationship between society and individuals and urges that this relationship is studied and pursued. The study revealed that the novelist was able to successfully embody the psychological contract of individuals within society and employ it so as to reflect the identity of those individuals and their groups within a specific framework. Moreover, he was able to draw the psychological contract, especially one (inferiority complex) of individuals and demonstrate its effects on the behaviors of members of society.